PERAN MAJELIS TAK’LIM MUSHOLA NURUL MUHTADIN DALAM PEMBENTUKANKARAKTER RELIGIUS DI DESA HIKUN - Pahrurraji Pahrurraji (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This research is motivated by the role of the Majelis Tak'lim Mushola Nurul Muhtadin in the formation of religious character in Hikun Village. The Majelis Taklim aims to invite and provide a positive impact so that they are not involved in negative actions, motivate them to participate in every religious activity, and train attitudes to be better, with the hope of being able to foster a religious attitude. This study aims to (1) Find out how the role of the Majelis Tak'lim Mushola Nurul Muhtadin in the formation of religious character in Hikun Village. (2) Find out the supporting and inhibiting factors of the role of the Majelis Tak'lim Mushola Nurul Muhtadin in the formation of religious character in Hikun Village. This study uses a qualitative descriptive approach and field research. Informants are ustadz, administrators, mosque youth, and members. The data collection techniques are obtained through observation, interviews, and documentation. Meanwhile, data analysis is done by means of data reduction, data presentation, and verification or triangulation. Based on the results of the study, it can be concluded that (1) The role of the Majelis Taklim Musola Nurul Muhtadin in forming religious character in Hikun Village, the author draws the conclusion that: the role of the Majelis Taklim in forming religious through Islamic educational values, routine religious studies conducted on Thursdays. Learning first begins with the recitation of the solawat, then the ustadz reads the Book of Nashaihul Ibad, after the recitation of the Book of Dhikr and praying together until finished. So that it can increase awareness of Islamic religious insight and knowledge, and can form religiousness well. (2) Factors that influence the role of the Majelis Taklim Musola Nurul Muhtadin in forming religiousness in Hikun Village, namely there are supporting and inhibiting factors, the supporting factors include: increasing faith. Meanwhile, the inhibiting factors are: the presence of other activities simultaneously with religious studies, laziness, and work.